Faktory ovlivňující přirozenou úrokovou míru na straně poptávky - Černý, Jakub; Zemplinerová, Alena; Potužák, Pavel; Vysoká škola ekonomická v Praze. Národohospodářská fakulta (2009)
I endeavour to identify the factors that influence the capital profitability in this work. So I study the usual objectives of the firms and how they reach these objectives, inquire into the ways how the firms assess their activities and describe the modern history of these assessments and then describe possibilities of the formation of the prices. I analyse the investing in human capital extra. And I endeavour to detect the influence of credits and market disequilibriums on investments.
Vedoucí práce: Alena Zemplinerová
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Způsob přístupu: Internet
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Národohospodářská fakulta, 2010
Rok obhajoby 2010
Keywords: ekonomie [obor bakal. práce]; kapitál; bakalářské práce; capital; bachelor's theses